(untitled) (World Economics and Finance Bulletin, 2022)
The current research aims to identify the impact of administrative decisionmaking methods on the performance of accountants and auditors in their drive to work and development. The amount of stability coefficient is "81.54". The researcher used the SPSS statistical package to analyze the results. The researcher reached a number of results, the most important of which is "that the manager possesses academic and professional qualifications" that has an active and influential role in developing work and increasing motivation among auditors and accountants. The researcher also recommends a number of recommendations, the most important of which is Issuing laws and following them up by the Ministry of Education to select general managers according to academic qualifications, professional experience, and administrative skills, and subjecting them to specialized training courses.